Chromatin status of apoptosis genes correlates with sensitivity to chemo-, immune- and radiation therapy in colorectal cancer cell lines - Benard, Anne (Apoptosis, 2014)
The apoptosis pathway of programmed cell death is frequently deregulated in cancer. An intact apoptosis pathway is required for proper response to anti-cancer treatment. We investigated the chromatin status of key apoptosis genes in the apoptosis pathway in colorectal cancer cell lines in relation to apoptosis induced by chemo-, immune- or radiation therapy. Using chromatin immunoprecipitation (ChIP), we measured the presence of transcription-activating histone modifications H3Ac and H3K4me3 and silencing modifications H3K9me3 and H3K27me3 at the gene promoter regions of key apoptosis genes Bax, Bcl2, Caspase-9, Fas (CD95) and p53. Cell lines DLD1, SW620, Colo320, Caco2, Lovo and HT29 were treated with cisplatin, anti-Fas or radiation. The apoptotic response was measured by flow cytometry using propidium iodide and annexin V-FITC. The chromatin status of the apoptosis genes reflected the activation status of the intrinsic (Bax, Bcl2, Caspase-9 and p53) and extrinsic (Fas) pathways. An active intrinsic apoptotic pathway corresponded to sensitivity to cisplatin and radiation treatment of cell lines DLD1, SW620 and Colo320. An active Fas promoter corresponded to an active extrinsic apoptotic pathway in cell line DLD1. mRNA expression data correlated with the chromatin status of the apoptosis genes as measured by ChIP. In conclusion, the results presented in this study indicate that the balance between activating and silencing histone modifications, reflecting the chromatin status of apoptosis genes, can be used to predict the response of tumor cells to different anti-cancer therapies and could provide a novel target to sensitize tumors to obtain adequate treatment responses.